Kinetic Modelling in Systems Biology - Oleg Demin (Chapman and Hall/CRC mathematical & computational biology series., 2009)
Systems biology, biological knowledge, and kinetic modeling -- Cellular networks reconstruction and statis modelling -- Edinburgh pathway editor -- Construction and verification of kinetic models -- Introduction to DBSolve -- Enzyme kinetics modelling -- Kinetic models of biochemical pathways -- Modelling of mitochondrial energy metabolism -- Application of the kinetic modelling approach to problems in biotechnology and biomedicine.